Reflecting on ICN2: was it a game changer? - Brinsden, Hannah (Arch Public Health, 2015)
At the Second International Conference on Nutrition (ICN2), November 2014, 170 member states endorsed the Rome Declaration on Nutrition and a Framework for Action. The Rome Declaration committed to ending malnutrition in all its forms while the Framework for Action offered 60 voluntary actions to help achieve this. These documents and ICN2 itself had the potential to be a major step forward for public health nutrition, addressing issues associated with today’s complex food system. This article reviews ICN2, its process, outputs and some of the gaps and weaknesses of the documents. ICN2’s legacy can be interpreted in two ways–a missed opportunity or one of broad aspirations which have yet to translate into meaningful action. The paper considers whether ICN2 could have adopted a more ecological approach to diet and nutrition, linking health and sustainability. While this fits the evidence, it would require a strong commitment to coherence and food system change, almost certainly a firm stance on some food corporate power, and resolve to champion health at the heart of economic policy. This ambitious agenda would require specific multi-actor and multi-level action, together with metrics and mechanisms for accountability. Coherent government policies and actions to tackle all manifestations of inappropriate diet, and to reframe the economic forces which shape such diets are urgently required. To achieve this, the public health movement needs to work closely with civil society, yet ICN2 showed that there is some reluctance to energise that combination. As a result, ICN2 must be judged a missed opportunity, despite having useful aspirations.